Chapter Деконструкция в романах Достоевского: замыслы, планы, подготовительные материалы, основной текст - Kazakov, Alexey (Biblioteca di Studi Slavistici, 2023)
Deconstruction in Dostoevsky's Novels: Ideas, Plans, Preparatory Materials, Main Text . This article examines the role of deconstruction in Dostoevsky's novels as a technique for bringing the ideological and psychological components of images into collision. These images are imbued with complex paradoxical meaning, revealing anthropological and philosophical issues in the writer's work. Crime and Punishment advances the theme of a need for crime in order to achieve the moral rebirth of the hero. Moving forward on this path, the novel dismantles both inner and outer limits in the space of the hero. In The Idiot, Dostoevsky links passionate and antagonistic motifs to the Christian idea, thereby deconstructing boththe entire ethical concept of Myškin and the narrative associated with it. In The Adolescent the main character is subjected to destructive motivational interventions.